(untitled) (Fiep Bulletin - online, 2012)
Sports injuries have highlighted studies which include football. For a long time it is known that football referee would be susceptible to the same injuries than the football players. Thus, the aim of this study was to analyze injuries situations in professional football referees. The sample was composed of 12 female referees from Catarinense Football Federation (FCF), with 25,5 ± 4,2 years old, 58 ± 2,8 kg and 1,63 ± 0,05m of age, weight and height means, respectively, that were interviewed during 2011 pre-season. We established three situations that a referee could be injured and if this injury would be considered a sports injury: during physical evaluation, in a training session or in a match. Of the entire sample surveyed, two referees claim to have suffered some type of sports injury in one of the situations described above. Two injuries were identified. All occurred during the training of refereeing. For these data, we can conclude that football referees do not get injured during the game or physical test, the most frequent occurrence of injury during training.